Developing teaching material for descriptive writing subject by using think pair share model in elementary school - Farida Ariani; Reflianto Reflianto; Nora Afnita (Fakultas Ilmu Pendidikan UNP)
The aim of this research was to develop a teaching material of descriptive writing by using cooperative teaching model with think-pair-share type based on its validity, practicality and effectiveness. Three items of the analysis covered a content feasibility analysis, language analysis and layout analysis. The method of this study was research and development approach with Defining, Designing, Developing, and Disseminating (4-D) model. Instrument of this research used the observation sheets, field notes, questionnaire, interview form and focus group discussion. The result of research showed that developing teaching material for descriptive writing lesson by using think pair share model can be a good product. This teaching material product has been valid and feasible and has been passed the content analysis, language analysis, layout analysis and practical by experts’judgment and empirical studies. After doing some trial of this product can be concluded that the product was more effective to improve students’ descriptive writing skill and can be more practical for Indonesian Language teachers of elementary school to use that. This product was expected become a prefer choice by teachers in the implementation of descriptive writing lesson for the fourth grade students of elementary school level.